1964
DOI: 10.1111/j.1558-5646.1964.tb01609.x
|View full text |Cite
|
Sign up to set email alerts
|

On Models Predicting Abundance of Species and Endemics for the Darwin Finches in the Galápagos Archipelago

Abstract: 339In a previous report to this journal (1963) we made conclusions on the processes of speciation and production of endemics among the Darwin finches in the Galapagos Archipelago. The conclusions were inferred from multiple-regression analysis wherein four independent variables of the insular environment were quantified and tested for respective abilities to predict species data. The analysis was an attempt by linear regression to discover (a) the environmental determinants of insular variation in the species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

1967
1967
2002
2002

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…The avifauna of the Galapagos Islands has provided a fertile testing ground for evolutionary and biogeographic theory (Swarth, 1934;Lack, 1947Lack, , 1969Bowman, 1961Bowman, , 1963Hamilton and Rubinoff, 1963, 1964, 1967Grant, 1986;Harper, 1987). This avifauna offers the best example of insular divergent evolution for which the entire, or nearly entire, species assemblage resulting from natural processes still exists.…”
Section: Introductionmentioning
confidence: 98%
“…The avifauna of the Galapagos Islands has provided a fertile testing ground for evolutionary and biogeographic theory (Swarth, 1934;Lack, 1947Lack, , 1969Bowman, 1961Bowman, , 1963Hamilton and Rubinoff, 1963, 1964, 1967Grant, 1986;Harper, 1987). This avifauna offers the best example of insular divergent evolution for which the entire, or nearly entire, species assemblage resulting from natural processes still exists.…”
Section: Introductionmentioning
confidence: 98%
“…
Rubinoff (1963, 1964) have studied isolation, number of species, and endemism in relation to the Darwin's finches of the Galapagos archipelago, and have concluded that, contrary to the view of Bowman (1961), the contention of Lack (1947) that there is a marked correlation between degree of isolation and production of endemic forms, is upheld. In their studies, two measures of isolation were used: distance from the nearest finchinhabited island ( X , ) , and (as used by Bowman) distance from Indefatigable, an island near the center of the archipelago ( X , ) .
…”
mentioning
confidence: 95%
“…Using the same method, showed that elevation was the major factor influencing numbers of plant species on the Galapagos islands, and (Hamilton et a]., 1964;Hamilton and Armstrong, 1965) that in the case of polyphyletic assemblages of bird species (resulting from repeated colonizations) on archipelagos in the East Indies, East Central Pacific, West Indies and the Gulf of Guinea, area of island is the major predictor of species numbers (equivalent of U,) , when considered along with elevation of island and various measures of isolation.…”
mentioning
confidence: 99%
“…In their studies, two measures of isolation were used: distance from the nearest finchinhabited island ( X , ) , and (as used by Bowman) distance from Indefatigable, an island near the center of the archipelago ( X , ) . By multiple regression analysis, Hamilton and Rubinoff showed that X S explained more of the variation in both total number of finch species on an island ( Y , ) and number of endemies on an island ( Y 2 ) than did X4, when these two factors only were considered; moreover X s was the prime "mover" of Y 1 and Y2 when these two factors were considered together with area of island, and floral diversity of island (the factor regarded as of prime importance by Bowman), or even when elevation of island and area of adjacent island were also included.Using the same method, showed that elevation was the major factor influencing numbers of plant species on the Galapagos islands, and (Hamilton et a]., 1964;Hamilton and Armstrong, 1965) that in the case of polyphyletic assemblages of bird species (resulting from repeated colonizations) on archipelagos in the East Indies, East Central Pacific, West Indies and the Gulf of Guinea, area of island is the major predictor of species numbers (equivalent of …”
mentioning
confidence: 99%
“…Using the same method, showed that elevation was the major factor influencing numbers of plant species on the Galapagos islands, and (Hamilton et a]., 1964;Hamilton and Armstrong, 1965) that in the case of polyphyletic assemblages of bird species (resulting from repeated colonizations) on archipelagos in the East Indies, East Central Pacific, West Indies and the Gulf of Guinea, area of island is the major predictor of species numbers (equivalent of…”
mentioning
confidence: 99%